Kesalahan Penggunaan Kata Bantu Bilangan Bahasa Mandarin pada Siswa Indonesia Tingkat Prapemula - Trihardini, Ayu (Lingua Cultura, 2015)
The purpose of this study was to analyze Indonesian breakthrough level students’ errors in using Mandarin measure words. The collected data were the errors made by students of Prodi Pendidikan Bahasa Mandarin UNJ who attend Conversation II course (CEFR A1/breakthrough) on written and oral utterance. This study used Zhou Xiaobin’s research design in Mandarin measure words error analysis, with the Carl James model of identification errors. The result of this study shows Indonesian students’ errors in using Mandarin measure words can be determined as follows: omission, misselection, misordering, and blends. Furthermore, this study proves that there are systematic errors made by students with different mother tongue and at the same level of learning Mandarin. The research results can be used to develop Mandarin measure words teaching techniques based on error analysis.